Terminalia arjuna in Chronic Stable Angina: Systematic Review and Meta-Analysis - Navjot Kaur; Nusrat Shafiq; Harish Negi; Avaneesh Pandey; Srinivas Reddy; Harpreet Kaur; Neelima Chadha; Samir Malhotra (Cardiology Research and Practice)
Background. Terminalia arjuna is a popular Indian medicinal plant with its bark been used for over centuries as cardiotonic. The bark has been found to contain several bioactive compounds including saponins and flavonoids. A number of experimental and clinical studies have been conducted to explore therapeutic potential of Terminalia arjuna in cardiovascular ailments specially in patients of coronary heart disease. A number of narrative reviews have been done but no systematic review has been conducted to date. Objective. To systematically review and conduct a meta-analysis on the available literature evaluating the efficacy of Terminalia arjuna in patients of chronic stable angina. Study selection. We included randomised, pseudo-randomized and before-after comparative studies which compared Terminalia arjuna/commercial preparation of Terminalia arjuna with current standard/ conventional treatment regimens in patients with chronic stable angina. Findings. Studies were found to be of poor methodological design. We found no significant difference in the Terminalia arjuna group as compared to control arm in the outcomes for which we were able to pool data and undertake meta-analysis. Conclusions. Currently, the evidence is insufficient to draw any definite conclusions in favour of or against Terminalia arjuna in patients of chronic stable angina. Further, well-controlled multicentric clinical trials need to be conducted in large number of patients to explore the therapeutic potential of Terminalia arjuna if any.